Diagnostic hysteroscopy in a procedure room setting compared to diagnostic hysteroscopy in the operating room - Oraif, Ayman (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: To examine patients’ perceptions of and satisfaction with diagnostic hysteroscopy with endometrial biopsy in a procedure room/office setting as compared to diagnostic hysteroscopy with dilation and curettage (D&C) performed in the operating room (O.R.). Methods: This comparative quality improvement study contrasts diagnostic hysteroscopy with endometrial biopsy in a procedure room and diagnostic hysteroscopy with dilation and curettage in the operating room. 66 women participated in the study. Variables examined were: length of hospital stay, anesthesia and analgesia used, pain scores, recovery time, overall experience and satisfaction associated with the procedure. Results: The O.R. group spent on average an additional 2 hours and 21 minutes in hospital compared to the procedure room group. The procedure room group received local blocks without the presence of an anaesthetist whereas the O.R. group received a range of intravenous (I.V.) medications given by an anaesthetist in addition to a local block. There was a slight increase in perceived pain among the procedure room group immediately following the procedure. However, no difference was observed between the pain scores collected upon discharge. More women from the O.R. group missed work due to their procedure compared to those in the procedure room group. Those from the procedure room group were able to return to their normal activities much sooner than those in the O.R. group and all of them indicated that they would prefer the same location in the future. A quarter of the patients in the O.R. group would prefer to have it performed in the procedure room, instead of the OR in the future Conclusions: Diagnostic hysteroscopy is currently considered a valuable investigational tool for endometrial abnormalities and abnormal uterine bleeding. Most of these procedures can be performed in a procedure room setting without I.V. sedation or pre-operative narcotics. In our experience, a utero-sacral block using lidocaine is quite effective in controlling discomfort while passing various instruments through the internal cervical os. These techniques result in good visualization of the endometrial cavity, adequate and appropriate endometrial sampling with tolerable discomfort. The patients spend less time in the hospital, experience a much faster recovery and have less pre-operative restrictions.